2013
DOI: 10.1186/1423-0127-20-90
|View full text |Cite
|
Sign up to set email alerts
|

Caspase 3 involves in neuroplasticity, microglial activation and neurogenesis in the mice hippocampus after intracerebral injection of kainic acid

Abstract: BackgroundThe roles of caspase 3 on the kainic acid-mediated neurodegeneration, dendritic plasticity alteration, neurogenesis, microglial activation and gliosis are not fully understood. Here, we investigate hippocampal changes using a mouse model that receive a single kainic acid-intracerebral ventricle injection. The effects of caspase 3 inhibition on these changes were detected during a period of 1 to 7 days post kainic acid injection.ResultNeurodegeneration was assessed by Fluoro-Jade B staining and neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…The activation of caspases is an additional process described during epilepsy (Niquet et al, 2007;Tzeng et al, 2013). Previous studies in mice (Wang et al, 2008b) reported that neurodegeneration and caspase-9 activation peaked 3 days after SE induced by pilocarpine and then gradually went down at 7-14 days.…”
Section: Discussionmentioning
confidence: 98%
“…The activation of caspases is an additional process described during epilepsy (Niquet et al, 2007;Tzeng et al, 2013). Previous studies in mice (Wang et al, 2008b) reported that neurodegeneration and caspase-9 activation peaked 3 days after SE induced by pilocarpine and then gradually went down at 7-14 days.…”
Section: Discussionmentioning
confidence: 98%
“…The expression of activated caspase‐3 was greater in GG than in specimens from patients with DNT, suggesting that GG are more susceptible to the pathological effects of chronic seizures. Accordingly, several experimental animal studies have provided evidence of caspase‐3 activation, in both glial and neuronal cells, following induction of status epilepticus [39–41]. In GG, caspase‐3 labelling positively correlates with age at surgery and the duration of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…The vulnerability of CA3 pyramidal neurons may be due to the abundant high-affinity KA-binding sites of this region (Tzeng et al 2013). …”
Section: Aberrant Hippocampal Neurogenesis and Hippocampal Damage Aftmentioning
confidence: 99%